Analisis Dampak Pemberian Tugas Tambahan kepada Guru Non Kompetensi terhadap Kinerja Layanan Pendidikan di SMKN 1 Tanjung - Rizza Maria Ulfa; Pusfita Hunaeda; Mohamad Mustari (Action Research Journal, 2026)
This study aims to analyze the management of educational human resources (HR) in assigning additional tasks to teachers at SMKN 1 Tanjung. The focus of the study is directed at the suitability of teacher competencies to the additional tasks assigned and their impact on the performance of educational services. This study uses a qualitative approach with data collection techniques such as in-depth interviews, documentation, and literature studies. The results indicate that the limited number of human resources with the appropriate qualifications and competencies is a major obstacle in implementing additional teacher tasks. This condition causes difficulties in carrying out main tasks and functions optimally. The resulting impacts include increased teacher workloads, decreased quality of educational services, and less effective performance of work units in schools. This study emphasizes the importance of implementing competency-based HR management through competency mapping, improved training programs, and the procurement of specialized professional education personnel to support the effectiveness of educational management